Literature Study of Cross-Cultural Size Comparisons Against Personality Traits - Charli Sitinjak (Yayasan Ilomata, 2023)
After more than a century of research at the university, personality traits have been fully studied and measured, thanks to the work of many researchers. The Big Five is one of the most popular personality tests. It was created using an ethical approach, which says that personality traits should be measured in the same way in all cultures. But as the effects of different cultures grow and researchers learn more, ethical approaches to measuring personality are increasingly questioned. In anthropological research, emic approaches emphasizing the importance of specific cultural methods have been studied. This method is used to create the Big Six and Big Seven scales below. These measurements have been tested and found to be more accurate and valid for measuring personality traits in the right group of people. So, this study is intended to provide a literature review that summarizes how personality traits are defined, the specific content and development of such measurements using ethical and emic approaches, measurement problems based on relevant research, and several other things to think about. About when assessing personality traits using an etic and EMIC approach.